PENDAMPINGAN ENGLISH CLUB SEBAGAI UPAYA PENINGKATAN KETERAMPILAN BERBAHASA INGGRIS SISWA DI SMP AL-FARUKI - Amelia, Riza; Natasha, Harum; Putriani, Zelly (Universitas Islam Negeri Sultan Syarif Kasim Riau, 2025)
This community service program aimed to enhance junior high school students’ English-speaking skills through assisting the English Club at SMP Al-Faruki. This program was designed to support students' interests and talents in speaking English. The program was conducted for five days, from June 19 to 24, 2023. Various activities such as news reading, reading through story strips, story-telling, English debate, dan fun speaking games, were employed to build students’ confidence and speaking abilities. Evaluation was conducted through qualitative analysis namely, observation and rating of speaking performance of pre-test and post-test. The results revealed that most of the students became more confident in using English after the program. The program also had a positive impact on student motivation and enthusiasm toward the English Club. Thus, the programs implemented in this community service activity could be continued as part of extracurricular activities recommended for students who are interested in enhancing their speaking skills outside the classroom.